KEPUASAN PELANGGAN MENGINAP DI HOTEL BERBINTANG DI DAERAH ISTIMEWA YOGYAKARTA - Sutomo, Maskuri (BISMA: Jurnal Bisnis dan Manajemen, 2012)
The research uses to the management economics approach, especiallyservice marketing management and its methods are survey by using cross sectiondata. Unit analysis in the research is customer at star hotel in Daerah IstimewaYogyakarta (DIY). Data will be obtained by spreading questionnaires and directinterview with 300 respondents. The research samples are 12 stars hotel in DIYwhich are stated by using systematic sampling. Data will be analyzed by usingImportance-Performance Analysis. The result of research shows customer have notmaximum satisfaction at stars hotel in DIY. This indicated higher customerexpectations for personal contact, supporting the physical facilities and equipmentcompared to the performance perceived by customers